The Effectiveness of a Designed Program Via Quiz Creator for Training Teachers to Design Electronic Exams, and Their Opinions About It - Alabdulla, Fawaz; Hameed, Walaa (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to investigate the effectiveness of suggested program in providing skills of designing the electronic exams by QuizCreator . The sample consists of 50 teachers of first stage teachers in Jablah, and it has been selected deliberately from teachers who can use computer well. The tools represent a pre-post performance test with review list, a training program about skills of designing electronic exams by QuizCreator, and a questionnaire, the results were the following: (1) The effectiveness of the training program, where the teachers got higher degrees in the post performance test. (2) The preeminence of teachers who their experience is less than 5 years over other teachers in the sample in the post test, and their opinions were more positive about the program. (3) The preeminence of college graduated teachers over those of institutes in the pre-performance test, and their opinions were more positive about the program.